The Setting Time of Polyether Impression Materials after Contact with Conventional and Experimental Gingival Margin Displacement Agents. Issue 2 (22nd June 2016) - Nowakowska, Danuta; Raszewski, Zbigniew; Ziętek, Marek; Saczko, Jolanta; Kulbacka, Julita; Więckiewicz, Włodzimierz
Abstract: Purpose: The compatibility of chemical gingival margin displacement agents with polyether impression materials has not been determined. The aim of this study was to evaluate the setting time of polyether impression elastomers after contact with conventional and experimental gingival displacement agents. Materials and Methods: The study compared the setting time of two polyether impression materials: medium body (Impregum Penta Soft) and light body (Impregum Garant L DuoSoft) after contact with 10 gingival displacement agents, including 5 conventional astringents (10%, 20%, and 25% aluminum chloride, 25% aluminum sulfate, and 15.5% ferric sulfate) and 5 experimental adrenergics (0.1% and 0.01% HCl‐epinephrine, 0.05% HCl‐tetrahydrozoline, 0.05% HCl‐oxymetazoline, and 10% HCl‐phenylephrine). As many as 120 specimens (60 light body and 60 medium body) were mixed with 20 μl of each of 10 gingival displacement agents, and the time to achieve maximum viscosity was measured with a viscometer. The setting times of these specimens were compared with the control group of 12 specimens, which were polymerized without contact with the displacement agents. The experiments were performed in two environments: 23°C and 37°C (± 0.1°C). Individual and average polymerization time compatibility indices (PTCI) were calculated. Data were analyzed by 2‐way ANOVA (α = 0.05). Results: The evaluated chemical displacement agents from both groups changed the setting time of light‐ and medium‐body PE. The negative individual PTCI values achieved astringent (20% aluminum chloride) with two PE in both temperature environments. The average PTCI values of the experimental displacement agents at laboratory and intraoral temperatures were significantly higher than the conventional agents. Conclusions: The present findings suggest that experimental retraction agents can be recommended clinically as gingival margin displacement agents with minimal effects on the setting time of medium‐ and light‐body polyether impression materials; however, direct contact of chemical displacement agents and polyether impression materials can be avoided.